2018
DOI: 10.1097/anc.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Syphilis

Abstract: The paucity of research, which focuses on CS, is most likely due to ethical concerns related to infants as research participants and provides an opportunity for future research. Future research could focus on factors that focus on maternal-fetal/maternal-child transmission of CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
2
21
0
5
Order By: Relevance
“…The incidence of congenital syphilis has also increased in other countries, such as the United States, which showed a considerable increase in rates over the same period. 6 , 19 A recent systematic review concluded that screening for pregnant women infected with syphilis contributes to reducing the incidence of congenital syphilis. 20 In 2016, the Ministry of Health implemented new strategic actions for the reduction of congenital syphilis in Brazil, thought precisely by the growing number of cases the country had been presenting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of congenital syphilis has also increased in other countries, such as the United States, which showed a considerable increase in rates over the same period. 6 , 19 A recent systematic review concluded that screening for pregnant women infected with syphilis contributes to reducing the incidence of congenital syphilis. 20 In 2016, the Ministry of Health implemented new strategic actions for the reduction of congenital syphilis in Brazil, thought precisely by the growing number of cases the country had been presenting.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The lack of medication and the epidemiological scenario that hit the country may possibly have led to an inadequate pharmacological treatment that, in turn, resulted in an increase in the rate of vertical transmission and an increase in neonatal morbidity and mortality. 6 However, the lack of medication no longer affects Brazil. According to the 2017 Syphilis Bulletin, penicillin was prescribed in 88.9% of cases for treatment of syphilis during pregnancy in 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em pacientes com SC tardia, podem ser vistos os sinais de Higoumenakis e de Auenbrugger e as juntas de Cluntton. 3 Com isso, nota-se que a SC pode causar vários desfechos sérios. 4 Ressalta-se que a incidência mundial de SC diminuiu entre o período de 2012 e 2016, embora a subnotificação causada pela falta de testes ou relatórios em vários países possa ter influenciado esse cenário.…”
Section: Introductionunclassified
“…Segundo dados da Organização Mundial da Saúde (OMS), na América do Norte, os casos de sífilis primária e secundária aumentaram de 0,9 para 1,9 por 100000 mulheres entre 2012 e 2016 e, de forma semelhante, os níveis de infecção de sífilis congênita cresceram de 8,4 para 15,5 casos por 100000 nascimentos, totalizando um aumento de 86,9% nesse mesmo período 8 . Além disso, estudos indicam que a sífilis congênita corresponde a, aproximadamente, 50% dos recém-nascidos com sequelas físicas, sensoriais e de desenvolvimento e que fatores socioeconômicos tem grande influência sobre sua incidência⁴ʾ¹⁴.…”
Section: Introductionunclassified